Assessment Framework for Next – Level Leadership Role Readiness in Retail Middle Management - Apipunnakul, Ganyapak; Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The objective of this study was to propose a next-level-leadership-role-readiness assessment framework for use in retail management. A qualitative-participatory approach was used for the research, with data collected using appreciative-inquiry-based interviews with middle managers in the retail industry (n = 20) and analyzed using a thematic analysis approach. The findings identified eight core competencies: strategic implementation, time management, people development, professional proficiency, entrepreneurship, commitment, change management, and innovation. These core competencies were drawn from the content analysis inter-coding and reviewed by the experts to develop a drafted framework for next-level leadership role readiness assessment. The draft framework includes competencies, other factors to be measured, a recommended implementation approach, and an approach for integrating the leadership role readiness assessment into the career development path of managers within the organization. The study focused on retail middle manager level based in Thailand. The results provide practical insights into how organizations can assess leadership readiness in a consistent and standardized way, offering a significant benefit. Further opportunities for research include implementing and testing the drafted framework and extending it to other organizational levels.